Kinetic Analysis of Biogas Production from Cow Manure Waste - Tsaqif, Farhan Fadlurohman; Erlina, Laras; Putra, Afshar Rehansyah; Akram, Felda; Syaichurrozi, Iqbal (World Chemical Engineering Journal, 2025)
Biogas is the result of decomposing organic waste that can be used as alternative energy. One of the organic waste that has the potential to produce biogas is livestock waste. The purpose of this scientific article is to see the results of kinetic models on secondary data processing of biogas volume acquisition/day. This scientific article was conducted by processing secondary data on biogas production at several pH variations (N1 = 7.17, N2 = 7.22, N3 = 7.24) using several kinetic models, namely the Gompertz model, logistic model, and first-order model. The best results are obtained in the logistic model, where the objective function value is the smallest. For each variation of N1, N2, and N3, the SSE values obtained are 458.37, 423, and 309. For the Gompertz and logistic models have the same graphical shape which is sigmoid-shaped or "s" shaped, which indicates that there are three phases in the formation of biogas, namely the pause phase, the rapid growth phase, and the stable growth phase. For the first-order model, it has a linear graph shape which states that in this model, there is a simplification of stages, namely only the hydrolysis stage which follows a first-order pattern.